Risk considerations for Brazilian tailings dam closure - Ritchie, DG; Baumgardner, Z (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
The January 25, 2019 failure of the Corrego de Feijao tailings dam in Brumandinho, Brazil owned by Vale S.A. resulted in 270 lives lost along with significant environmental and cultural heritage impacts. Pursuant to this failure the Public Ministry of the State of Minas Gerais (MPMG) initiated a series of dam safety audits to enhance dam safety oversight and effect change within the Brazilian mining industry, concurrently with the Brazilian National Mining Agency (ANM) issuing legislation in February 2019 requiring the removal or stabilization and decharacterization (deregistration) of all upstream tailings dams. This paper discusses the dam closure risk considerations and experience on various dam safety audits carried out by SLR Consulting (Canada) on behalf of MPMG. The audits involved dams raised by a variety of methods including the upstream method founded on deposited tailings. In general, the focus of the technical audits included geotechnical characterization of the dam and foundation, dam design and construction stewardship, public and worker safety, and emergency preparedness, from the perspectives of both Brazilian regulations and international tailings and dam safety practice. Case studies are presented within three groupings to highlight various experiences: modifications introduced for works that had been carried out prior to commencing the audits, works designed and executed during the audit oversight, and design and planning considerations for closure works that are in progress for high-risk upstream-raised tailings dams. For all cases, the long-term risks, credible failure modes, and operational controls during construction are discussed. The Group 1 case studies highlight the importance of a holistic, long-term risk management perspective. The dam discussed was decharacterized as a mining dam prior to commencing the dam safety audits but was deemed susceptible to credible failure modes including slope instability, erosion, and spillway downcutting. In 2022 the Brazilian national mining agency updated the administration of mining dams to include a minimum of two years of monitoring after completion of the closure works. Notwithstanding, Vale is implementing improvements to the dam as part of their evolving dam safety governance practices in response to audit recommendations. Closure activities for the two dams in Group 2 involved low risk. Closure was planned and successfully completed within the period of the audits. For these dams, design decisions were made after comparing alternative closure scenarios by long-term objectives, constructability, dam safety during construction, and environmental and social considerations. Construction vibration testing was carried out to ensure construction-induced vibrations did not impact adjacent dams. The Group 3 case studies discuss design and planning decisions related to decharacterization of three upstream-raised tailings dams, two of which are at emergency levels. Prior to commencing construction dam breach inundation studies were carried out, emergency preparedness and response plans updated, and citizens in the potential inundation zone were evacuated and/or back-up or emergency containment dams were built. Construction planning included consideration of remotely-operated construction equipment, dam instrumentation (geophones, seismographs and piezometers) to detect construction-induce vibrations that could trigger tailings liquefaction, water management, and planning of staged excavations.
Keywords: tailings liquefaction; dam removal; construction-induced vibrations; dam safety governance Vargem Grande is currently at Emergency Level 1 because of susceptibility of failure due to tailings liquefaction. Since 2019; Vale has conducted continuous improvements to the dam including pumping out the pond; reconstitution of the foundation drainage outlet; surface drainage improvements and installation of sediment control measures. Channels have been cut into the tailings to better manage drainage from the beaches and from within the upper tailings. Due to the upstream construction; the Vargem Grande Dam raises will be removed. Vale began mass tailings excavation in 2022. The work is scheduled to take approximately 5 years after which time the starter dam will remain in place for sediment control. Safety concerns during closure construction include dam slope instability due to tailings liquefaction or softening due to induced vibrations or high water levels. The relatively complex dam foundation conditions that have been approached differently by various reviewers; auditors and designers has resulted in various opinions of the dam safety conditions. Similarly; poor installation of dam instrumentation and a lack of stewardship of the data obtained has resulted in uncertainty regarding stability. The stability assessment has improved with a better understanding of the phreatic level obtained after installing new piezometers. The safety factor values calculated for slip surfaces within the tailings are now marginally less than the required minimum for static loading conditions. Vale and the Engineer of Record were able to establish a stable; phreatic level since installing a series of electric piezometers with proper surface seals. Improved geotechnical characterization has increased confidence in planning for closure. Existing dam instrumentation has been used to establish background phreatic and vibration levels as part of the routine dam safety surveillance program. As part of the improved drainage works the spillway invert was lowered and appears to be adequately sized to pass the design flood resulting from the PMP. Vale has adopted a pragmatic approach to excavating the tailings progressively; starting from the upstream side of the basin and working towards the dam in order to take advantage of experience that will be gained through the work to minimize risk. Based on lessons learned from Fernandinho; channel excavation and lowering of the water table before excavating the partially drained tailings are being implemented successfully. A sump was established in natural ground prior to commencing significant tailings excavation. Drainage channels discharging to the sump are completed in a grid fashion prior to commencing tailings excavation (Figure 6). The water level is maintained approximately 5.5 m below working tailings and drains readily to the sump which is about 3 m lower. Safe limits have been set for the overall slope height and inclination to limit shearing and strain within the tailings to mitigate static liquefaction concerns. Vale conducted a construction equipment vibration test on the Vargem Grande tailings to mitigate liquefaction risks and are currently working to establish vibration monitoring between the work area and the dam to improve vibration attenuation relationships in order to allow for possible future optimization. Lowering the phreatic level significantly below the working tailings surface has served to reduce the risk associated with construction induced vibrations. B3/B4 has been classified as a high damage potential; high risk tailings impoundment dam with a maximum height of about 55 m and crest length 210 m. The dam contains tailings and/or sediment with an impounded volume in the order of 2.7 Mm3. A mine waste stockpile (PDE X) is located in the upstream region of the B3/B4 tailings impoundment. A second mine waste stockpile (PDE Oeste) is present above the right abutment. The cross-sectional geometry of B3/B4 has been inferred from boreholes put down for As-Is reporting and routine dam safety assessments. There are no active operations at B3/B4 other than monitoring and surveillance; maintenance; and closure activities that commenced in late 2020. The dam was at Emergency Level 3 because the static slope stability requirements are not satisfied; and the retained solids are in a contractive state and therefore prone to static and dynamic (seismic) liquefaction. The emergency spillway is also not sufficient to protect the dam by safely passing runoff from extreme storm events. At this time; the dam appears to be stable and no significant deformation trends have been noted in routine surveillance inspections or through dam instrumentation and there are no indications of imminent failure. A watershed diversion channel was completed in 2019 at the right flank of the facility (Figure 4) to reduce the runoff inflow to the B3/B4 pond. Vale has lowered the pond significantly and sufficient installed pumping capacity can maintain the pond below the spillway invert except in extreme storm conditions. Three deep dewatering wells were installed in the right flank of the impoundment in 2019; however these have not been effective in terms of lowering the phreatic level in the tailings significantly. The primary risk considerations for implementing closure are water management and limiting construction induced vibrations and shearing that could trigger tailings liquefaction. The spillway appears to be of reasonable size to pass the design storm; however; spillway failure is considered to be a credible failure mode because the erosion protection is not considered to be adequate. The excavation has been planned to facilitate storing the storm runoff within the excavation. Prior to commencing any excavation Vale constructed a rockfill backup dam approximately 10 km downstream of B3/B4 that provides adequate storage to contain a total release of the B3/B4 tailings; the dam fill; and a portion of PDE X along with storm runoff reporting with the released tailings. Citizens within the potential inundation zone were evacuated and work on the dam and within the potential inundation zone is performed using remotely operated equipment. In this sense the work did not proceed until there was no risk to citizens or workers. The decommissioning plan involves removal of B3/B4 and the upstream tailings slowly in stages so as to avoid triggering liquefaction. The initial works involved removing a portion of PDE X to expose natural ground (weathered rock) at the toe of the stockpile thereby creating a separation between the tailings and mine waste. Maximum slope height and inclination limits have been set for excavation in the tailings to limit shearing risk; and instrumentation has been installed in the dams and around the perimeter of the tailings to measure the vibration levels induced by the construction equipment to mitigate liquefaction risks. The current dam instrumentation is appropriate for detecting conditions that could lead to the failure modes identified; except seismic liquefaction. Diversion channel and PDE Oeste slope inspections are carried out to identify concerns related to slope instability and ditch blockage; particularly in the rainy season. Approximately 2/3 of the decharacterization work has been safely completed to date. Detailed stress-strain modelling is being performed by consultants to Vale in order to optimize the later stages of the excavation planning in the narrower portions of the valley. The case studies highlight the need to maintain a long-term perspective; consider a range of alternatives; and maintain flexibility to manage dam closure risks considering knowledge and data gaps. All dam closure planning needs to consider the level of confidence in terms of understanding the dam design basis and performance. Risk assessments are recommended to identify design and construction execution risks during the planning phase. Contingency planning should address known risks prior to starting closure construction to facilitate quick responses and limited impacts to dam safety; worker safety and schedules. For upstream raised dams constructed on contractile tailings or dams with other significant inherent risks; construction planning should be practical; methodical; and flexible. Dam instrumentation and data quality are paramount to ensure safety. Effective monitoring plans should take into account the loss and replacement of dam monitoring instruments as construction activities move locations and the risks change. The regulatory requirements for closure of mining (tailings) dams in Brazil generally consist of the mining proponent submitting a closure plan outlining the dam characteristics; operational history; closure; and rehabilitation measures proposed; and the monitoring associated with such; albeit for a relatively short period. Corporate governance such as adopted by Vale and the principles outlined in PRI et al. (2020) and ICMM (2021) are considered to be necessary to mitigate long-term risks.